PENGELOLAAN LABORATORIUM BAHASA PADA IMPLEMENTASI KURIKULUM 2013 - Sukartini Sukartini; Rohiat Rohiat; Aliman Aliman (UNIVERSITAS BENGKULU, 2017)
The objective of the study as the answer of the problem are; how are the planning of the management, the usages ,the evaluations of the language laboratorium in implementing the curriculum 2013. The method of the research is qualitative descriptive by collecting the data, observation, interview and documentation. The subject of the research is the language laborant of Senior High School number two South of Bengkulu. The conclusion of the study is the planning done by the language laborant have been followed the norms of managing the ideal and integral language laboratory. The management of language laboratory done by the laguage laborant are the implementation that is required by the curriculum 2013. The evaluation and monitoring of the management of the language laborant runs well and routine as programmed, and it has been set as the real condition.